THE HISTORY AND TRANSFORMATION OF NEURO-LINGUISTIC PROGRAMMING - Khasanov, Jahongir (Foreign Languages ​​in Uzbekistan (JOURNALFLEDU.COM), 2023)
Neuro-Linguistic Programming (NLP): method of acting on human consciousness and knowledge, linked to an influence at the level of ideology and Ideas about the World concerning the human mind and moral conscience. In many circles of psychologists, there is the conviction of the pseudo-scientific nature of this method or the conviction that its use causes superficial and short-term effects; despite the lack of full support in scientific circles, this notion has already entered the vocabulary of psychology, education, business and various systems of the socalled "self-development", and it continues to be popularized. NLP or neuro-linguistic programming refers to a whole set of techniques (dissociation, reframing) and methods aimed at promoting the personal development of the individual. This article investigates NLP in detail: its principles, its history, its benefits, and the progress of a session.